AGAMA DAN PERDAMAIAN (Pengaruh Agama Terhadap Peran Jemaat Gereja Protestan Maluku Bethel Dalam Membangun Perdamaian Pasca Konflik 2002 Di Kota Ambon) - , Sisca Pattipawaej, Dr. Nanang Pamuji Mugasejati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to describe and explain how the influence of religion on the role of the Maluku Protestant Church Bethel Church in Post-Conflict Peace building 2002 in Ambon city. The background is that the selection of topics